Effect of Online Reviews, Brand Image, and Trust on Purchase Intention Case Study: Purchasing Beauty Products Via Marketplace - Erni Wahyuni; Rika Syahmewah Munthe; Amron Zarkasih; Irhamna Mandili (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The beauty sector is a very large market today. The number of beauty influencers who become role models for women is a trigger for their followers to follow the style of the influencers so that the interest in beauty products is increasing rapidly. For producers and practitioners in the beauty business sector, knowing the driving factors for the emergence of an intention to buy a beauty product is an absolute must, so the company feels the need to know the triggers for the emergence of an intention. In this era of high digital media usage, online reviews from buyers who have purchased online are very important for potential buyers who are looking for beauty products to be used as references before buying. A good brand image is also a factor that is considered by potential buyers, then trust is certainly something vital in the emergence of purchase intentions. This study aims to examine the effect of online reviews, brand image and consumer trust on the intention to buy beauty products via online. This study uses a quantitative approach, the data collection method uses a survey method through an online questionnaire. The sample in this study includes 250 women who have purchased beauty products online via the marketplace. The results of this study indicate that all hypotheses are supported and have a positive and significant influence in influencing women's purchase intention of beauty products via the marketplace.